Evaluation of Anti-angiogenic Activity of Centella asiatica Water Extract on Chick Embryo Chorioallantoic Membrane Induced by bFGF - Iwan Sahrial Hamid; Ngakan Made Rai Widjaja (Indonesian Journal of Cancer Chemoprevention, 2013)
Angiogenesis is a physiological process that involves the formation of new blood vessels. In the cancer growth process, angiogenesis acts by supplying nutrition and oxygen for the cancer cells, carries metabolic waste and biological end product of cancer cells. Therefore the spread of cancer cells to the surrounding cells and tissues is accelerated. The occurrence of angiogenesis shows a change in cancer cell status, from dormant to malignant. Cancer cells induce the formation of angiogenesis through the secretion of various growth factors such as Vascular Endothelial Growth Factor (VEGF) and basic Fibroblast Growth Factor (bFGF).Currently many people turn into treatment using natural materials. One of the natural materials used for cancer therapy is pegagan (Centella asiatica). In this research 25 embryonated chicken eggs (ECE) were divided into five treatment groups. Treatment group I as the control received 60 ng bFGF, treatment group II received neither bFGF nor pegagan leaves (Centella asiatica) water extract, and  treatment groups III-V received 60 ng bFGF and  C. asiatica leaves water extract of 75, 90 and 110 µg.  Nine days old ESE were inoculated with bFGF and extract at the same time and then were incubated at 380C for three days to allow the formation of blood vessels in embryonated chicken egg chorioallantoic membrane.  Observations were performed microscopically and macroscopically by counting the new blood vessels formed around paper disc. Analysis on VEGF expression were conducted to define the role of angiogenesis growth factor.Research results showed a significant difference of treatment with Centella asiatica water extract on the number of new blood vessels formed. Centella asiatica water extract at the dose of 110 µg was the highest in inhibiting the formation of new blood vessels. Centella asiatica water extract also inhibited the expression of VEGF.Keywords : Centella asiatica, antiangiogenic, Corio Allantois Membran, VEGF